Sektor Pertambangan: Dampak Positif dan Dampak Negatif terhadap Perekonomian Bagsa - Musdar Muhammad; Bahrun Talib; Roif Hidayatulloh (MENAWAN : Jurnal Riset dan Publikasi Ilmu Ekonomi, 2026)
Indonesia possesses abundant natural resources, particularly in the mining sector, which play a crucial role in supporting the national economy. Commodities such as coal, nickel, gold, copper, as well as oil and natural gas contribute significantly to government revenue, exports, employment creation, and infrastructure development in mining-producing regions. Over the past decade, rising global demand for new and renewable energy has positioned nickel as a strategic commodity, thereby encouraging increased investment and the strengthening of downstreaming policies through the development of mineral processing facilities. However, mining activities also generate negative impacts, including environmental degradation, declining public health conditions, and social inequality in communities surrounding mining areas. Therefore, although the mining sector has the potential to drive economic growth and increase local incomes, its management must be guided by the principles of sustainable development to ensure that economic benefits do not come at the expense of environmental preservation and social welfare.